FRAGMENTATION OF POLYTENE CHROMOSOMES OF CHIRONOMUS STRIATIPENNIS (KIEFFER) AS A MARK OF HEAVY METAL TOXICITY IN AQUATIC HABITATS - T. MIDYA; P. SARKAR; S. BHADURI; A. MAZUMDAR (The Bioscan, 2013)
The adults of Chironomids are though terrestrial, but in immature stages they pass their days in water. In aquatic bodies the flies at their larval stages live about 18-20 days and any incompatible situation in the habitats affects growth and development of the larvae. A study on the polytene chromosomes of the salivary gland cells of the larvae of C. striatipennis indicated that high level of toxicity due to heavy metals in the habitats led to fragmentation of their polytene chromosomes. Culturing of the larvae of this species in the laboratory with 30 mg/Kg of Cd with soil in the culture bed exhibited fragmentation of their polytene chromosomes in certain cases. In this toxicity impact the fourth polytene chromosome appeared to be more affected. Hence, a variation of response of different chromosomes of the fly to toxicity may be suggested.